Architectural rendering of the Forestry Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, 1908 - Nowell, Frank H., 1864-1950 (1908)
Photograph of an architectural drawing. On verso of image: Forestry Building, Alaska-Yukon-Pacific Exposition PH Coll 727.339 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number